MRI Findings in Patients with TMJ Click - Mahrokh Imanimoghaddam; Azam Sadat Madani; Elahe Mahmoudi Hashemi (Mashhad University of Medical Sciences, 2013)
Introduction: It has been shown that joint click, an initial and common finding in internal derangement (ID), respond to neither conservative treatment nor surgical intervention. This raises the question as to whether it must be treated in the absence of other pertinent signs and symptoms, so the aim of this study was to investigate and compare the MRI findings of TMJ in both normal subjects and patients with click, in order to determine the importance of click in predicting TMJ pathological changes. Methods: A total of 26 patients with clinical symptoms of disk displacement with reduction (DDwR) according to RDC/TMD were compared to 14 normal subjects in terms of their MRI findings, including disk displacement, effusion, condylar osteoarthritic changes and disk deformities. Results: Out of 80 joints in total (52 affected joints in 26 patients and 28 joints in control group), 48 were shown with normal disk position in MRI whereas 28 (35%) and 4 (5%) were categorised as DDwR and (disk displacement without reduction) DDwoR, respectively. Statistically significant correlations were established between the following pairs of variables in order: Click and disk displacement, effusion and disk displacement, disk displacement and effusion with disk deformity. Conclusion: The correlation between the presence of click and disk displacement, disk deformity and effusion emphasizes the importance of MRI for an accurate diagnosis and development of an appropriate treatment plan in these cases and shows that clinical examination is not sufficient for these purposes.